Study on airfoil performance in unsteady flows - Teo, Alvin Zhen Wei. (2012)
Aircraft accident rates may be on the decline with the improvement in technology and maintenance practices. However, there is still room for improvement as the number of passengers on aviation transport is set to grow and increase in the near future. There is still a general lack of understanding how an aircraft behaves in unsteady flows, or gust. Most wind tunnels can only generate steady flows. However, this does not accurately represent real life conditions, where the wind speed and direction may change almost instantaneously. Hence, this project looks into developing a suitable mechanism to generate gust in wind tunnels. The first aim of this project is to design a gust generator operating on oscillating airfoils in order to generate unsteady gusts. The desired output of this gust generator is to produce a sinusoidal flow. The second aim is to conduct a parametric study on the different factors, such as the oscillation frequency, the oscillation amplitude, and the various distances, that would affect the output and the performance of this gust generator. The flow is studied by observing the variation on the forces exerted on a symmetric airfoil. This preliminary study enables more complex flow patterns to be studied in future, with the results from the sinusoidal gust forming the basic building blocks. This can be done with the Fourier series and the super position theorem, which allow the results from various simple gust patterns to be added up to predict the result of a complex gust pattern. This is in the hopes of better understanding aircraft performance in gust conditions, thus leading to better safety records.